Solitary fibrous tumor of the pineal gland: a case report and review of the literature - He, Yixiao; He, Pengchen; Wang, Anqun; Ji, Yuzhu; Xie, Gang; Zou, Lili (Frontiers in Oncology, 2024)
Solitary fibrous tumor (SFT) is a type of fibroblastic neoplasm that can occur in various parts of the body, with SFT of the pineal gland being exceedingly rare. We report the case of a 58-year-old male presenting with recurrent hiccups, acid reflux, and headache. Magnetic resonance imaging revealed an occupying lesion in the pineal region, suggestive of a neoplastic process. Intraoperatively, the lesion was located in the pineal region, exhibiting a grayish-red color, and was largely resected. Pathological examination confirmed the diagnosis of solitary fibrous tumor (CNS WHO Grade 1). Postoperatively, the patient was supplemented with radiotherapy, and long-term follow-up showed no signs of recurrence or metastasis.